2022
DOI: 10.1007/s11356-021-18454-7
|View full text |Cite
|
Sign up to set email alerts
|

Green bond as a new determinant of sustainable green financing, energy efficiency investment, and economic growth: a global perspective

Abstract: The purpose of the study is to test the role of green bond financing on energy efficiency investment and economic growth. To achieve the study objective, fuzzy decision-making modeling technique is applied. The results revealed that bank loans are now the main source of financing for energy efficiency projects. Project-based financing might be replaced with Energy Performance Contracts (EPC) warranting energy efficiency investment. Moreover, green banks invest both public and private funds in energy efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 46 publications
2
30
0
3
Order By: Relevance
“…The coefficients of trade indicate that the amount of green output decreases with time the structure of how much and how much energy is used in industrialization. We had expected these results, and they confirm our suspicions about China’s excessive urbanization and reliance on coal consumption ( Chien et al, 2021 ; Lee and Lee, 2022 ; Ning et al, 2022 ). According to the EDU coefficient, a high degree of traditional education is associated with low green productivity.…”
Section: Resultssupporting
confidence: 68%
“…The coefficients of trade indicate that the amount of green output decreases with time the structure of how much and how much energy is used in industrialization. We had expected these results, and they confirm our suspicions about China’s excessive urbanization and reliance on coal consumption ( Chien et al, 2021 ; Lee and Lee, 2022 ; Ning et al, 2022 ). According to the EDU coefficient, a high degree of traditional education is associated with low green productivity.…”
Section: Resultssupporting
confidence: 68%
“…From 1998 to 2002, the notion of green finance was developed. According to Ning et al (2022) , Green finance is a vital link between the financial and environmental industries and critical financial innovation in the quest for environmental conservation. The green finance theory underwent a steady evolution between 2000 and 2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the objective rules of ecosystems and ecological processes, Jin et al (2021) contend that humans must control and regularize the natural environments in which they live. Ning et al (2022) said that the mechanical study technique shows that the economic-centric development model will ultimately lead to the nations’ economic crisis if the ecological rules are violated, and the ecosystem is damaged. The ecological economy can only be realized if methodology and ecology are incorporated into economics and harmoniously develop the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research by Bamisile et al (2021) states that while green finance significantly influences polluting industries, it also significantly stimulates environmentally friendly initiatives. It was found that the mechanism by which GF improved agricultural innovation performance was examined by Ning et al (2022). From 2012 to 2019, Saeed Meo and Karim (2021) used the green patent quantities of Chinese companies as a quasi-natural experiment to see if the green finance policy had any effect on corporate green innovation.…”
Section: Green Economic Recoverymentioning
confidence: 99%